2023
DOI: 10.1096/fj.202301417r
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sphingosine kinase 1 in p53KO thymic lymphoma

Fabiola N. Velazquez,
Jeffrey L. Stith,
Leiqing Zhang
et al.

Abstract: Sphingosine kinase 1 (SK1) is a key sphingolipid enzyme that is upregulated in several types of cancer, including lymphoma which is a heterogenous group of malignancies. Treatment for lymphoma has improved significantly by the introduction of new therapies; however, subtypes with tumor protein P53 (p53) mutations or deletion have poor prognosis, making it critical to explore new therapeutic strategies in this context. SK1 has been proposed as a therapeutic target in different types of cancer; however, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Many sphingolipid mimetics have issues with solubility and delivery. Additionally, PK studies that have been conducted on sphingolipid inhibitors have revealed reduced stability in vivo and short plasma half-life [61,75,116]. Nanoliposomes are currently being explored to improve delivery and stability for several sphingolipid mimetics and inhibitors.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…Many sphingolipid mimetics have issues with solubility and delivery. Additionally, PK studies that have been conducted on sphingolipid inhibitors have revealed reduced stability in vivo and short plasma half-life [61,75,116]. Nanoliposomes are currently being explored to improve delivery and stability for several sphingolipid mimetics and inhibitors.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%